===================================
Simplifying - Solution and Explanation
===================================
Hello! So...
We are given the following to simplify:
![7√(28x^6) -5√(63x^6)](https://img.qammunity.org/2023/formulas/mathematics/high-school/n7g5dy4eak2ikugyjagybkbdeqz0ddwglf.png)
_________________________________________________
To solve this, we must simply simplify.
![7√(28x^6) =14√(7) x^3](https://img.qammunity.org/2023/formulas/mathematics/high-school/75h71vrugstnexwc2jvm2fwkr53tpzy2aw.png)
![5√(63x^6)=15√(7)x^3](https://img.qammunity.org/2023/formulas/mathematics/high-school/kxek06uqb21dmenwo6tz6ztlpac24sqe4u.png)
![=14√(7)x^3-15√(7)x^3](https://img.qammunity.org/2023/formulas/mathematics/high-school/yrngaia2zetybpoy6gigv0wt1kfgym4fjg.png)
Now, add the similar elements:
![14√(7)x^3 -15√(7) x^3=-√(7)x^3 \\](https://img.qammunity.org/2023/formulas/mathematics/high-school/89ps93lfnmcoorpyt1makokucyrfhy3cum.png)
Now, considering we are assuming all variables are positive in this situation, we need to convert the negative into a positive solution.
![=-√(7)x^3](https://img.qammunity.org/2023/formulas/mathematics/high-school/xlxtsya3ig6100dal7uij098coxmmtvarh.png)
![= x^3√(7)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ec5sv2ykfzpu5j7z694el0b8tdiz7fqfz1.png)
^Hence, our solution.^
______________________________________________________
Hope this helps! If so, please lmk! Thanks and good luck!